Peningkatan Perekonomian melalui Potensi Desa Sumbergiri, Kecamatan Ponjong, Kabupaten Gunung Kidul - Pratama, Yohanes Mario (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Sumbergiri is one of the villages in Kapanewon Ponjong, Kabupaten Gunungkidul, Special Region of Yogyakarta. The potential of the village in Sumbergiri encompasses the results of nature (both farming, agriculture, etc.) and the tourist objects of Telaga Kepleng. One of the goals it set up was to raise the economic value of Sumbergiri village to the country. In addition, there is a need to give literature to the Sumbergiri village community about the planning of the development of a tourist resort in Telaga Kepleng and the cooking results of pedestrians and corn rice through pocket books as media information. Data retrieval such as information on village potential, Sumbergiri village profile data, mining tourism work program, and the content of pedestrian and corn rice pieces taken through journals, articles, and information from the Internet that is designed in the form of videos and e-books. The results of the first work program are e-book and video potential of the Sumbergiri village. While the second output discussed about pocket book which contains explanations of Peyek Pedari and corn rice to the composition contained therein. Hopefully, the results of the two work programmes can be used in the development of Sumbergiri Village in the future.